THE ROLE OF THE ZAKAT MANAGEMENT ORGANIZATION (ZMO) IN RESTORING THE CONDITION OF POST-DISASTER VILLAGES IN NORTH LOMBOK REGENCY - Hanafi, Syahrul (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
The earthquake that occurred in NTB province resulted in many deaths, refugees, and damaged buildings. The earthquake disaster also damaged the community's economic, social, and educational conditions. One of the areas most severely affected by the earthquake was North Lombok Regency (KLU). Many non-governmental organizations, including zakat management organizations (ZMO), have participated in distributing aid and restoring the condition of villages in KLU. This study aims to determine the role of ZMO in restoring the condition of villages in KLU. This research is qualitative research with a descriptive approach. The results of the study found that: ZMO began to distribute disaster assistance in KLU during the phase when the disaster occurred, starting from steps 1) rescue and search for victims; 2) evacuation of victims. Then in the post-disaster phase, starting from steps 1) donations and services, 2) consolidation and 3) reconstruction and rehabilitation. The last phase carried out by ZMO is the pre-disaster phase, where the steps taken are disaster preparedness.